H-Index Predicts Academic Rank Among Orthopaedic Surgery Faculty - Ramon A. Arza, BS; Alexander W. Richards, BA; Ajay S. Potluri, BS; Matthew J. Hadad, MD; Glenn D. Wera, MD (JBJS Open Access)
Background:. Research productivity, education, and clinical performance have become increasingly central to faculty promotion decisions in orthopaedic surgery. The Hirsch index (h-index) has emerged as an objective tool for quantifying academic impact, but its relationship with academic rank in orthopaedic surgery remains incompletely understood. Methods:. We analyzed faculty data from the top 50 academic orthopaedic surgery programs ranked by Doximity. We identified faculty members from institutional websites and collected academic metrics from Scopus, including h-index, publication counts, first-author publications, last-author publications, career length, and m-index (h-index divided by the career length). We used a multivariate analysis and recursive partitioning to identify predictors of senior academic rank (associate or full professor). Results:. Of 2,744 faculty reviewed, 1,520 academic orthopaedic surgeons met the inclusion criteria. The median h-index was 15 (interquartile range [IQR]: 7-27), and the median career length was 19 years (IQR: 13-28). In multivariate analysis, h-index and career duration emerged as the strongest predictors of senior academic rank. Multivariate recursive partitioning identified the h-index, number of publications, first-author publications, and career length as influential predictors. Faculty at institutions ranked 1 to 25 demonstrated significantly higher academic productivity across all metrics than those ranked 26 to 50 (p < 0.001). The trajectory of research productivity shows a consistent increase with career duration, with the m-index plateauing mid-career. Conclusions:. Our findings indicate that the h-index and career length are significant predictors of senior academic rank. Academic productivity was higher at programs ranked 1 to 25 by Doximity compared with those ranked 26 to 50. While productivity metrics generally increase with career duration, the m-index plateaus in mid-career. Level of Evidence:. Level III, Prognostic Study. See Instructions for Authors for a complete description of levels of evidence.